Meningkatkan Pemahaman Belajar Pada Materi Sifat Wajib Bagi Allah siswa Kelas III SD Negeri 23 Pangkalpinang Melalui Metode Pair Checks - Iswanto, Yuni; Patimah, Patimah (LENTERNAL: Learning and Teaching Journal, 2023)
This study aims to find out about the application of the pair checks method in improving students' understanding of learning in Islamic Religious Education sub-material of the mandatory attributes of Allah in third grade students of SD Negeri 23 Pangkalpinang. This study uses classroom action research (Action Research) by applying two cycles. Each cycle consists of four stages, namely: planning, implementation, observation, and reflection. Collecting data in this study using observation and test techniques. The sample in this study was the third-grade students of SD Negeri 23 Pangkalpinang, amounting to 33 people. Data analysis used descriptive qualitative. The results showed that the understanding of student learning outcomes using pair checks can be categorized as high, this is illustrated by the average student learning outcomes, namely in the first cycle the average is 66.67 while in the second cycle the average is 75.45 and completeness the minimum is very significant which can be stated from the percentage gain for each cycle, namely 63.64% in the first cycle, increasing to 93.94% in the second cycle. So, it can be stated that the use of the Pair Checks method shows a significant relationship in achieving the targeted learning outcomes.